Extreme Event Statistics in Dst, SYM‐H, and SMR Geomagnetic Indices - A. Bergin; S. C. Chapman; N. W. Watkins; N. R. Moloney; J. W. Gjerloev (Space Weather)
Abstract Extreme space weather events are rare, and quantifying their likelihood is challenging, often relying on geomagnetic indices obtained from ground‐based magnetometer observations that span multiple solar cycles. The Dst index ring‐current monitor, derived from an hourly average over four low‐latitude stations, is a benchmark for extreme space weather events, and has been extensively studied statistically. We apply extreme value theory (EVT) to two geomagnetic ring current indices: SYM‐H (derived from 6 stations) and SMR (derived from up to 120 stations). EVT analysis reveals a divergence between the return level found for Dst, and those for SYM‐H and SMR, that increases non‐linearly with return period. For return periods below 10 years, hourly averaged SYM‐H and SMR have return levels similar to Dst, but at return periods of 50 and 100 years, they respectively exceed that of Dst by about 10% and 15% (SYM‐H) and about 7% and 12% (SMR). One minute resolution SYM‐H and SMR return levels progressively exceed that of Dst; their 5, 10, 50, and 100 year return levels exceed that of Dst by about 10%, 12%, 20% and 25% respectively. Our results indicate that consideration should be given to the differences between the indices if selecting one to use as a bench mark in model validation or resilience planning for the wide range of space weather sensitive systems that underpin our society.